2020
DOI: 10.1097/bpo.0000000000001381
|View full text |Cite
|
Sign up to set email alerts
|

Midterm and Long-term Follow-up After Surgical Reconstruction for Lateral Polydactyly of the Foot With Mosaic-like Alignment of the Phalanx Bones

Abstract: Background: The phalanx bones in several cases of lateral polydactyly of foot revealed complicated alignment with radiographic findings revealing medial-protrusion and lateral deviation of the middle phalanx. We previously defined such cases as showing “mosaic-like alignment” and demonstrated favorable postoperative outcomes using our surgical procedure. The aim of this study was to evaluate the midterm and long-term postoperative outcomes in such cases. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…Uda et al [14] reported that a valgus deformity persisted when the medial toe of the phalangeal type was excised. Iba et al [17] reported a surgical procedure in which the alignment between the distal and proximal phalanges for the excision of the sixth toe and medial excess bone from the fifth toe was independent of the middle phalanx alignment and restored ligamentous stability. Nakamura et al [6] asserted that this deformity could be corrected by trimming the joint face and tacking the medial soft tissue around the joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uda et al [14] reported that a valgus deformity persisted when the medial toe of the phalangeal type was excised. Iba et al [17] reported a surgical procedure in which the alignment between the distal and proximal phalanges for the excision of the sixth toe and medial excess bone from the fifth toe was independent of the middle phalanx alignment and restored ligamentous stability. Nakamura et al [6] asserted that this deformity could be corrected by trimming the joint face and tacking the medial soft tissue around the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Iba et al . [17] reported a surgical procedure in which the alignment between the distal and proximal phalanges for the excision of the sixth toe and medial excess bone from the fifth toe was independent of the middle phalanx alignment and restored ligamentous stability. Nakamura et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although various surgical methods for postaxial polydactyly of the foot have been described, 2,4,12,14 there is little information available, especially with respect to predictors of surgical outcomes. In addition, some authors have attempted to classify postaxial polydactyly to assist in determining the most appropriate treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…MPPP was defined as a specific type of postaxial polydactyly in which the duplication starts at a common proximal interphalangeal (PIP) joint. 10 In this study, 37 feet of 37 patients were included. Four patients presented with bilateral postaxial-type polydactyly, but the duplication on the opposite side was at the proximal phalanx or metatarsal level on simple radiography; hence, only 1 foot was included in the study.…”
Section: Patient Selectionmentioning
confidence: 99%
“…7,8 In countries with negative cultural atmospheres about polydactyly, parents of patients prefer performing the operation in early childhood. 9,10 Owing to the same tendency in South Korea, operative treatment is performed at around 1 year of age when children start to walk and have increased outdoor activities.…”
mentioning
confidence: 99%